Combined Intestine and Kidney Transplantation in a Patient With Encapsulating Peritoneal Sclerosis: Case Report. Issue 12 (13th November 2013) - Waghray, A.; Nassar, A.; Hashimoto, K.; Eghtesad, B.; Aucejo, F.; Krishnamurthi, V.; Uso, T. D.; Srinivas, T.; Steiger, E.; Abu‐Elmagd, K.; Quintini, C.
Abstract Encapsulating peritoneal sclerosis (EPS) is a rare but devastating complication of peritoneal dialysis characterized by fibrosis and calcification of the intestine that, in severe cases, can progress to intestinal failure and total parenteral nutrition dependency. Medical and surgical interventions carry a poor prognosis in these patients. We describe a case of a 36‐year‐old female with end‐stage kidney disease and severe EPS not amenable to surgical intervention who underwent a combined intestinal and kidney transplantation. At 3 years posttransplantation, the patient has normal intestinal and kidney function. This represents, to our knowledge, the first report of severe EPS and end‐stage kidney disease treated with a combined transplant.